Effect of some plant oils on some Biological aspects of the beetle cowpea weevil Callosobruchus maculatus(Fab)Coleoptera : Bruchidae)) - Alaa AL-Awady (University of Thi-Qar Journal of Science, 2019)
Present study aimed in the evaluated t the effectiveness of some plants oils peppermint, Saad and cotton againsteggs and adult cowpea beetle Callosobruchus maculatus after an hour and after 24 hours on bean seeds after treated it with oils and used in different concentrations, 5.10, 2.5 ml / liter. The results showed that the best oils ieffected inthe mortality percent of the eggs.The leaf of peppermint oil was reached of 64.55 %followed by cotton oil where thepercent was 51.21% and the lowest percent at 37.77%.for -Saad, oil.On the other hand peppermint oil was mosteffected on th destruction of Adult at 48.38% and followed by cfotton oil at the percent 34.94% followed by Saad, oilat 33.88%.The period time the most effected on the percent mortality after 24 hour on mortality significant on percent of adult after one hour was reached 62.23% for peppermint oil and the percent for Saad oil at 38.88% whilethe lowest mortality percent. For the cotton oil at 27.77% ,after one hour was the most mortality perecent for adult34.44% of peppermint oil and 28.88% for Saad oil and 24.22% of the cotton oil .